The Effectiveness of the Biblio Counseling Model to Increase the Adversity Quotient of Adolescents - Irman Irman; Silvianetri Silvianetri; Fadhilah Syafwar; Putri Yeni; M Habibullah Silvir; Zubaidah Zubaidah (Universitas Islam Negeri Mahmud Yunus Batusangkar, 2023)
The main problem is experienced by institutionalized youth is a low level of adversity quotient (AQ). The impact is that it is difficult to develop the life skills needed in this century. One treatment that can be given to increase teenagers' adversity quotient is Biblio counseling. This research aims to test the effectiveness of Biblio Counseling in increasing teenagers' Adversity Quotient. This research uses a quantitative approach, specifically Quasi Experimental. The data analysis used was a pretest-posttest control group design. The research population was 100 teenagers at the Harapan Youth Development Social Institution in Padang Panjang. The research sample was 30 people taken randomly. The research instrument uses an adversity response scale with a validity of 0.857 and a reliability of 0.903. Data analysis using independent T-test. The research results show: (1) Biblio counseling is an interesting technique for orphaned teenagers to find solutions to the life problems they are experiencing, and (2) Biblio counseling is effective in increasing the AQ of institutionalized teenagers. It is recommended that social services utilize Biblio Counseling services as treatment in increasing the AQ of orphaned teenagers.